LAND SUBSIDENCE MONITORING ON THE UNDERGROUND MRT CONSTRUCTION AREA IN JAKARTA, INDONESIA - Bernike, Chara; Nagai, Masahiko; Osawa, Takahiro (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 14 No 2 (2020), 2020)
Space utilization for measurement of the changes of Earth’s surface is an alternative monitoring technique. Covering a large area with better spatial resolution, comparable accuracy and costly low compared with conventional measurement have made SAR technology more popular in monitoring the subsidence. Land subsidence is the vertical movement of the land surface mainly triggered by fluid extraction, load of construction, geological condition, natural compaction or tectonic activity. Previous researchers have found that Jakarta has experienced land subsidence for decades. On the other hand, rapid urban growth and severe congestion problem in Jakarta are also crucial issues. By providing the first MRT subway, it is expected to be solved the congestion problem. Persistent Scatterer Interferometry Synthetic Aperture Radar (PSInSAR) is one of method to identify the deformation with millimeter accuracy. It was perfectly useful for studied on the land subsidence in consequence of the first MRT subway project in Jakarta. The land displacement monitoring along MRT subway trajectory has been acquired by processing Sentinel 1 and ALOS PALSAR-2. This study was able to investigate the land subsidence by using SARPROZ. Finally, the results of this study indicated that land subsidence occurred in the construction area with the lowest land subsidence rate of -0.6 cm/year and the highest land subsidence rate was -7.3 cm/year. Keywords: PSInSAR; subway; land subsidence; MRT.